Anmeldelser - Damsholt, Inger (Danish Yearbook of Musicology, 1998)
Review of: Knud Arne Jürgensen: The Verdi Ballets (Premio internazionale Rotary Club di Parma „Giuseppe Verdi“ 4). Instituto nazionale di studi verdiani, Parma 1995.